Slaget om krigarkonungen: Hyllning, medier och rituella territorier - Lundström, Anna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
This article discusses the ritual celebration of the Swedish eighteenth century warrior king Charles XII. The celebration takes place in the 30th of November, the day of his death. The article is based on fieldwork and interviews with participants in the celebration. In their narratives they link ideology and their own personal destinies. In that process they incorporate their bodies as a vehicle for symbolizing their often violent struggle. By talking about people who have died as a consequence of manifest ideological standpoints, fields of tension are created in the narratives. These fields link together the personal struggle to become a victim and the sacrifice and martyrdom of others. The mass media plays an important role in shaping the form of the celebration in that the participants interact with photographers and journalists.